Reversible surface functionalisation of emulsion-templated porous polymers using dithiophenol maleimide functional macromolecules. Issue 70 (17th August 2017) - Eissa, A. M.; Wilson, P.; Chen, C.; Collins, J.; Walker, M.; Haddleton, D. M.; Cameron, N. R.
Abstract : Reversible, easy-to-monitor approach to the surface functionalisation of thiol–acrylate polyHIPEs that can be utilised in a wide range of applications. Abstract : A new facile and efficient route for the chemical functionalisation of thiol–acrylate polyHIPE materials with responsive macromolecules using the highly emissive dithiomaleimide (DTM) linker is demonstrated. Functionalisation is found to be reversible upon addition of a thiol-containing compound, glutathione, resulting in switchable surface properties including fluorescence and wettability, hence broadening the scope of applications.